Facial Recognition Door Lock Using Raspberry Pi - Anuar, Muhammad Haris Azman (Universiti Sains Malaysia, 2018)
There are many possible applications, hardware and devices that exist under the Ubiquitous Computing field. Facial recognition security system is one of key areas under this field. Facial recognition security system is widely used for identity verification due to its capability to measure and subsequently identify user for providing security, informal matching, law enforcement applications, user verification, user access controland is mostly used for recognition for various applications. Facial recognition is theability to detect and identify a person by characteristics on their face. Face is multidimensional that requires a lot of mathematical computations to detect and recognize. There are many methods for facial recognition that are already proposed but have low performance recognition capability, less accuracy rate, etc. Therefore, this task of the research is to develop a facial recognition security system with an improved accuracy rate and provide high performance of a facial recognition security system toaccess a building. This facial recognition security has been implemented on an embedded platform Raspberry Pi and OpenCV (Open Source Computer Vision Libraries). Raspberry Pi 3 Model B is used to implement open source code including debugging and testing. Focus for this project is implement facial recognition security with high accuracy rate and better performance recognition capability. Accuracy rate and recognition capability is one of important things for this Facial Recognition Door Lock Using Raspberry Pi.